Searching for Potential Biomarkers of Penthorum chinense Pursh by Extraction Method and HPLC-MS Analysis Integrated with Evaluation of Hepatoprotective Effect - Wan, Jin-Yi; Sun, Zong-Liang; Zhang, Yu-Zhen; Wei, Cai-Bing; Wang, Chong-Zhi; Zhou, Lian-Di; Zhang, Qi-Hui; Yuan, Chun-Su (Current Pharmaceutical Analysis, 2018)
Background: Penthorum chinense Pursh has a long history as a traditional medicine for the treatment of liver diseases in China. Despite its common use, investigations on the hepatoprotective components of P. chinense have not been carried out clearly. Experiment: Four extraction methods related to reflux, cold-soak, microwave and ultrasonic extraction were compared for optimum condition, combined with in vitro antioxidant activities and in vivo hepatoprotective effects to explore the chemical principles responsible for its liver protective effects. Result: Of four methods, the reflux extraction displayed the highest efficiency, producing the most abundant flavonoid of 82.36 mg/g (as rutin equivalents). Furthermore, among the 10 flavonoid constituents identified with their mass spectrometry data, HPLC analysis showed the contents of six major ones from reflux extraction were significantly higher, namely protocatechuic acid (1), catechin (2), 2,6- dihydroxyacetophenone-4-O-[4',6'-(S)-hexahydroxydiphenoyl]-β-D-glucose (3), pinocembrin-7-O-[3- O-galloyl-4'',6''-hexahydroxydiphenoyl]-β-D-glucose (PGHG) (4), quercetin-3-O-α-L-rhamnoside (5) and thonningianins A (Th A) (6). Compounds 2, 4, 5 and 6 exhibited potent antioxidant activity, while compounds 4, 5 and 6 remarkably prevented the elevation of alanine aminotransferase in an alcoholic liver injury mouse model. Hence, PGHG, quercetin rhamnosides and Th A could be considered as key active biomarkers of P. chinense for the treatment of hepatitis.
Keywords: antioxidant activity